2015
DOI: 10.1152/japplphysiol.01141.2014
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nitrate supplementation improves muscle oxygenation, O2uptake kinetics, and exercise tolerance at high but not low pedal rates

Abstract: Bailey SJ, Varnham RL, DiMenna FJ, Breese BC, Wylie LJ, Jones AM. Inorganic nitrate supplementation improves muscle oxygenation, O2 uptake kinetics, and exercise tolerance at high but not low pedal rates. J Appl Physiol 118: 1396 -1405, 2015. First published April 9, 2015 doi:10.1152/japplphysiol.01141.2014.-We tested the hypothesis that inorganic nitrate (NO3 Ϫ ) supplementation would improve muscle oxygenation, pulmonary oxygen uptake (V O2) kinetics, and exercise tolerance (Tlim) to a greater extent when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 60 publications
8
114
2
1
Order By: Relevance
“…It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation. Furthermore, several recent studies have observed improvements in physiological functioning and exercise performance in situations where type II muscle recruitment is likely to be high (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), which further supports the findings of this investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…It is therefore possible that elevated type II muscle Ca 2+ handling and muscle contractile function may have further contributed to the improved 1500 m performance observed in the present investigation. Furthermore, several recent studies have observed improvements in physiological functioning and exercise performance in situations where type II muscle recruitment is likely to be high (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), which further supports the findings of this investigation.…”
Section: Effects Of Brj On 1500 M Tt Performancesupporting
confidence: 89%
“…Recent data from murine models suggest that NO 3 − supplementation elevates blood flow and oxygenation (Ferguson et al 2013(Ferguson et al , 2015, and increases calcium (Ca 2+ ) handling protein expression and force production (Hernandez et al 2012) in type II muscle only (for review, see Jones et al 2016). Therefore, the beneficial effects of NO 3 − supplementation might be restricted to, or most pronounced during, exercise where type II fibers are predominantly recruited (Breese et al 2013;Bailey et al 2015;Coggan et al 2015), such as during short duration exercise where a higher relative work rate can be adopted (Essén 1978;Sale 1987). Additionally, hypoxia and acidosis-cellular conditions particularly prevalent at higher work rates (Richardson et al 1995;Robergs et al 2004)-are known to enhance the reduction of NO 2 − into NO (Modin et al 2001;Cosby et al 2003;Castello et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is evidence from murine model investigations that nitrate supplementation may enhance tissue blood flow [41,42] and muscle contractile function [9] preferentially in type II muscle fibres. It is therefore possible that nitrate supplementation is more effective during shorter more high-intensity exercise, during which these muscle fibres are more heavily recruited [9,[43][44][45]64], or else in individuals with greater distribution of type II muscle fibres [43]. The time-trial duration employed in this study (< 6 minutes) was considerably less than other investigations (~ 17 -48 minutes) which have not observed an ergogenic effect of nitrate supplementation in hypoxia [38][39][40], and may be important.…”
Section: Effect Of Nitrate Supplementation On Running Performance In mentioning
confidence: 76%
“…Moreover, nitrate supplementation has been demonstrated to elicit beneficial effects when the contribution of type II muscle towards force generation is high, including at fast but not slow muscle contraction frequencies [44], and during the transition from moderate to severe but not unloaded to moderate intensity exercise [45].…”
Section: Introductionmentioning
confidence: 99%
“…Participant characteristics: Five studies recruited young, non-smoking, healthy 135 participants [7,21,23,25,26], three studies were conducted in older healthy subjects [17,19,27],…”
mentioning
confidence: 99%